KEBHINEKAAN GLOBAL: IMPLEMENTASINYA DALAM PENDIDIKAN PANCASILA - Alfiyah, Siska Nur; Suneki, Sri (Civis : Jurnal Ilmiah Ilmu Sosial dan Pendidikan, 2025)
Global diversity is one of the important aspects that must be possessed by students. This is stated in the Pancasila Student Profile program. Global diversity will foster a sense of mutual respect, tolerance, and openness to other cultures. Global diversity has four elements, one of which is intercultural communication and interaction. This problem is caused by a lack of understanding of global diversity. The purpose of this study is to see how the application of intercultural communication and interaction as part of global diversity, especially in Pancasila Education. The research method used is a qualitative approach and is descriptive. The application of global diversity, especially the elements of intercultural communication and interaction in Pancasila Education, is in accordance with the provisions of the Ministry of Education and Culture. Meanwhile, from the school side, it is implemented through the title of the P5 work and school activities, namely cultural festivals and cross-cultural discussions. This received a positive response, where students became more confident in appearing in public and representing their respective cultures.